TRANSFORMASI KESADARAN MELALUI YOGA AKSARA - Ni Made Evi kurnia Dewi; Putu Agustiantini (Genta Hredaya: Media Informasi Ilmiah Jurusan Brahma Widya STAHN Mpu Kuturan Singaraja, 2023)
Literal yoga is a mental practice that is carried out through meditation involving the Onkara script. Literary yoga is a way to train the mind and transform consciousness. Ongkara in thought works as a bhija-mantra to build human consciousness at one point. Train the mind to stay focused on one object, and complete the activity of the mind like an ape constantly jumping from one object to another. Helps to release the attachment of mind awareness to its object, both material (all things that can be perceived by the senses) and mental (related to memory, emotion, perception, imagination). When a person is separated from the bondage of his objects, he will realize himself as his Paramasu and is also symbolized as Ongkara. As a result of practice, the script belongs to Siddhi. Siddhi is a manifestation of the transformation of personal consciousness to the Supreme consciousness, Siddhi is also a transformation of buddhi which is rajas-tamas into animal. The transformation of buddhi is more dominant in everyday life or attitudes with noble and wise characters which can later be used as role models and guidelines, guiding humans in living daily lives towards a peaceful, happy, physical and spiritual life, one form of siddhi development is astasiddhi.Keywords: literal yoga, meditation, siddhi